The Complementary Use of Experiments and Field Data to Evaluate Management Practices: The Case of Subjective Performance Evaluations - Patrick Kampkötter; Dirk Sliwka (Institute for the Study of Labor (IZA), 2015)
Most firms rely on subjective evaluations by supervisors to assess their employees' performance. This article discusses the implementation of such appraisal processes, exploring the use of multiple research methods such as the analysis of personnel records, survey data, and lab and field experiments to study them in detail. We argue that the complementary use of these methods helps to build a better understanding of how subjective evaluations are conducted and appraisal systems should be designed.
Keywords: D22; J33; M12; M52; 330; subjective performance evaluation; performance appraisals; management practices; experiments; field data; LPP